KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP DI BANDUNG BARAT - Harry Dwi Putra; Hikmal Setiawan; Devina Nurdianti; Indah Retta; Amaliya Desi (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
ABSTRACTThis study aims to analyze students' mathematical understanding ability. The research approach used is qualitative with an analytical descriptive method so that obtained the description of students' mathematical understanding ability. The instrument used is the test of mathematical understanding ability, interview guidance, and questionnaire that has been done validation. The test aims to obtain a picture of student error answers based on the scores obtained. Interview guide to obtain information about student's mistakes. Questionnaires to know students' interest in math. The subject of the research is the students of class VIII in one junior high school in Kabupaten Bandung Barat as many as 36 people. The results showed that students made a mistake in determining the characteristics of the rectangular building. Students cannot complete the calculation of area and around the rectangle correctly. The students' understanding of mathematical ability lies in the low criteria so that improvement needs to be made. Students who can solve mathematical comprehension problems enjoy math lessons.  Keywords: Mathematical Understanding Ability, Error Analysis